Evaluation of Functional Outcome of Proximal Humerus Fractures Treated with PHILOS Plate (Medicine Today, 2026)
Introduction: Proximal humerus fractures (PHFs) are common, particularly in the elderly, and their optimal surgical management remains a subject of ongoing debate. Locking plate technology, especially the Proximal Humerus Internal Locking System (PHILOS), has been developed to address challenges in osteoporotic and comminuted fractures by enhancing fixation stability. Aim of the study: To evaluate the functional outcome and complication profile of PHFs treated with PHILOS plating in a tertiary care setting. Methods: A prospective observational study was conducted on 32 patients with PHFs treated with PHILOS plate fixation. Demographic and clinical data were recorded, and patients were followed for a minimum of 6 months. Functional outcomes were assessed using the Constant-Murley Score and the Disabilities of the Arm, Shoulder and Hand (DASH) score. Subgroup analyses were performed based on fracture type (Neer classification), and associations between surgical timing, complications, and outcomes were analyzed statistically. Result: The mean age of patient was 55.4 ± 12.9 years, with males comprising 56.25% of the cohort. The majority of injuries resulted from low-energy falls (68.75%). Two-part fractures were the most common (37.5%), followed by three-part (40.63%) and four-part (21.88%) types. The mean Constant-Murley Score at final follow-up was 74.9 ± 9.1, with 43.75% of patients achieving excellent results. Functional outcomes were significantly better in 2-part fractures compared to 4-part fractures (p = 0.003). Complications occurred in 31.25% of patients, and were significantly associated with lower Constant scores (p < 0.001). Conclusion: PHILOS plating provides satisfactory functional outcomes in proximal humerus fractures, especially in less complex fracture patterns and when surgery is performed early. However, the presence of complications significantly compromises shoulder function. Careful patient selection, timely intervention, and postoperative rehabilitation are crucial for optimal outcomes.Medicine Today 2026, Vol.38 (1): 50-55